mathleaks.com mathleaks.com Start chapters home Start History history History expand_more Community
Community expand_more
{{ filterOption.label }}
{{ item.displayTitle }}
{{ item.subject.displayTitle }}
arrow_forward
{{ searchError }}
search
{{ courseTrack.displayTitle }}
{{ printedBook.courseTrack.name }} {{ printedBook.name }} Combining Linear Functions

Function Operation

Functions can be combined, through addition, subtract, multiplication, and division to create a new function. The resulting function can have similar or new characteristics, depending on the original functions and which function operation is used.

Combining Functions

Functions behave similar to numbers when they are combined to create new functions. Common ways of combining functions include addition, subtraction, multiplication and division.

Method

When adding or subtracting functions, it is possible to find the resulting function by combining like terms. If two functions, f(x) and g(x), are combined through addition or subtraction and one or both have a restricted domain, the domain of the resulting function is restricted to interval(s) where both f(x) and g(x) are defined.

Multiplication

When multiplying two functions, the Distributive Property can be used. Meaning, every term in one function is multiplied with every term in the other. If two functions, f(x) and g(x), are combined through multiplication and one or both have a restricted domain, the domain of the resulting function is restricted to interval(s) where both f(x) and g(x) are defined.

Division

When two functions are combined through division it is necessary to take into account that division by zero is undefined. As a consequence the domain of the resulting function is restricted to interval(s) where both functions are defined and where the denominator does not equal zero.
fullscreen
Exercise
Given the linear functions f(x)=3x+5 and g(x)=-x+2, find the function
h(x)=f(x)+g(x).
Show Solution
Solution
We add functions by combining like terms. Since g(x) begins with a negative term, we can put parentheses around it before adding.
h(x)=f(x)+g(x)
h(x)=3x+5x+2
h(x)=3xx+5+2
h(x)=2x+7
The new function, h(x), can be written as h(x)=2x+7.
fullscreen
Exercise
The functions f and g are given as f(x)=x4 and g(x)=2x1. Find h(2) if
h(x)=f(x)g(x).
Show Solution
Solution
To begin, we can write the rule of h(x) by multiplying f and g.
h(x)=f(x)g(x)
h(x)=(x4)(2x1)
h(x)=2x2x8x+4
h(x)=2x29x+4
Next, to find h(2), we'll substitute x=2 into the rule of h and simplify.
h(x)=2x29x+4
h(2)=22292+4
h(2)=2492+4
h(2)=818+4
h(2)=-6
Thus, h(2)=-6.